International Financial Statistics, June 2006. (International Financial Statistics; International Financial Statistics ;, 2006)
International Financial Statistics provides a complete library of continuously updated international statistics on all aspects of international and domestic finance. The monthly print edition contains over 1,000 pages of statistical data in each issue. It reports, for most countries of the world, current data needed in the analysis of problems of international payments and of inflation and deflation, id est, data on exchange rates, international liquidity, money and banking, interest rates, prices, production, international transactions, government accounts, and national accounts. Information is presented in country tables and in tables of area and world aggregates.